Evaluation of Pavement Condition Based on the Value of Surface Distress Index and Pavement Condition Index on the Road Section of Gedong Tataan - Kedondong, Pesawaran - Hidayat, Aditya Mahatidanar; Prasetyaningtiyas, Gayuh Aji (Dinamika Teknik Sipil: Majalah Ilmiah Teknik Sipil, 2023)
Good road infrastructure conditions can stimulate the economic growth of an area. Therefore, routine road maintenance is carried out by its administrators. One of the road sections that needs improvement is the Gedong Tataan - Kedondong road section. The Gedong Tataan - Kedondong section is a provincial road with a length of 16.67 kilometers. To predict the pavement condition on the road section, an assessment method is required for identification. This method is used as one of the tools to assess pavement damage on a road section, and the methods used are the Surface Distress Index (SDI) and the Pavement Condition Index (PCI). The research results show a PCI (Pavement Condition Index) value of 73%, indicating that the road pavement condition is very good, and routine maintenance is required. Meanwhile, with the SDI (Surface Distress Index) method, a value of 65 is obtained, indicating that the road falls into the fair category, and the appropriate treatment options include patching and overlay. Another implication is to allocate the budget wisely for road maintenance. Information from these two indices helps in determining improvement priorities. Routine maintenance can be a better investment in the long term than letting road conditions deteriorate.